METODE TA’LILI SEBAGAI ALAT IJTIHAD HUKUM ISLAM (IBTIKAR: Jurnal Studi Islam dan Sosial, 2024)
The study of Islamic law in the history of its development is carried out using the bayani, ta'lili and istishlahi approaches. Bayani focuses legal studies on linguistic rules, istishlahi on the beneficial aspects and ta'lili on the optics of the logical reasons behind a law. This research focuses its study on the ta'lili method considering the rules of fiqhiyah agreed upon by the jurists "law is centered on 'illat, if there is 'illat - then there is law, and if there is no 'illat - then there is no law". This research was conducted to determine the nature of 'illat and various types of 'illat in studying Islamic law. To find out the research object, this research was carried out in the form of library research where the data was collected through documentation studies of a number of literature that could provide information for the research. A number of data collected were analyzed for data availability and drawing conclusions. The research results show that illat is a logical cause that forms the basis of a law. The ta'lili method consists of ta'liliyah tasyri'iyah, ta'liliyah qiyasiyah and ta'liliyah istihsaniyah.